FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN RAWAT JALAN PUSKESMAS BANDAR PETALANGAN PELALAWAN TAHUN 2017 - Nany Librianty (Universitas Pahlawan, 2017)
Community service can be said to be good if the community can easily get services and procedures that are not long, cheap, fast and almost no complaints are given to them. The purpose of this study was to analyze the factors associated with patient satisfaction with outpatient health services in Bandar Petalangan Health Center in 2014. This type of research is quantitative with a Cross Sectional approach, with a population of 240 people and a sample of 150 respondents with accidental sampling technique. Processing data using the chi square test. The results showed that there was a relationship between outpatient registration services and the satisfaction of patients who went to the Puskesmas with a value of p = 0.001 and there was a relationship between physician services and outpatient satisfaction at the Puskesmas p = 0.001, there was a relationship between pharmacy services and outpatient satisfaction in Puskesmas. , p value = 0.001 and there is an environmental relationship between Puskesmas and outpatient satisfaction at the Pelalawan Bandar Petalangan Public Health Center in 2014. It can be concluded that there is a relationship between factors that affect patient satisfaction with outpatient health services at Bandar Petalangan Pelalawan Year 2017 Health Center. Puskesmas management must pay more attention to the performance of officers in the Bandar Petalangan health center in order to improve quality services for the community, so that the community is satisfied with the services provided.